Peran Guru dalam Membina Literasi Digital Peserta Didik pada Konsep Pembelajaran Abad 21 - handiyani, Mila Handiyani; Yunus Abidin (Elementary Teacher Education Program, Majalengka University, 2023)
Technological advances are so rapidly affecting various fields, one of which is education. Education cannot be separated from progress. As one of the innovators, teaching in schools should be carried out by following all the changes that exist. In fact, students' digital literacy abilities are known to be in the low category so that the learning needs of each individual are not optimally achieved. The purpose of this study as an analysis that utilizing information and communication technology that is growing rapidly can help students meet their learning needs. The research method was carried out by means of literature analysis, the authors looked for various reference sources to provide information about the benefits of digital literacy for students. The result is that good digital literacy skills can enrich themselves with knowledge by actualizing themselves in these technological advances. The role of the teacher in this case is certainly irreplaceable, but the teacher can guide the extent to which students can utilize technology on the positive side and to what extent they can minimize the possibility of deviating from the use of this technology